Efektivitas Token Ekonomi untuk Mengurangi Perilaku Agresif pada Anak Usia Dini - Hidayati, Rizkia (SOCIETIES: Journal of Social Sciences and Humanities, 2025)
Abstract. Aggressive behavior is a common issue among early childhood populations and may negatively affect children’s social, emotional development. This study aims to examine the effectiveness of a token economy intervention in reducing aggressive behavior in young children. A single-case study design was employed, involving a 5-year-old boy as the research participant. Assessment procedures included observations, interviews, document reviews, and psychological testing to obtain a comprehensive understanding of the participant’s behavior. The intervention was administered across 20 sessions and resulted in a noticeable decrease in aggressive behaviors. Continued support and active involvement from the surrounding environment are required to sustain the behavioral improvements achieved. Keywords: Aggresive behavior, token economy, early childhood